2016
DOI: 10.11604/pamj.2016.23.74.8688
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and use of emergency contraception among students of public secondary schools in Ilorin, Nigeria

Abstract: IntroductionUnintended pregnancy and unsafe abortion pose a major reproductive health challenge to adolescents. Emergency contraception is safe and effective in preventing unplanned pregnancy. The objective of this study was to assess the student's knowledge and use of emergency contraception.MethodsThis cross-sectional study was carried out in Ilorin, Nigeria, using multi-stage sampling method. Data was collected using pre-tested semi-structured self-administered questionnaire. Knowledge was scored and analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…The age at first sexual debut for some respondents in this study was less than 10 years. Early sexual debut is a widely reported phenomenon in many parts of Africa [2527]. However, the possibility of unplanned adolescent pregnancy and sexually transmitted infections (STIs) is a source of concern in this study.…”
Section: Discussionmentioning
confidence: 90%
“…The age at first sexual debut for some respondents in this study was less than 10 years. Early sexual debut is a widely reported phenomenon in many parts of Africa [2527]. However, the possibility of unplanned adolescent pregnancy and sexually transmitted infections (STIs) is a source of concern in this study.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, the use of EC varies from as low as 13 % [ 18 ] to as high as 52 % [ 14 ], however, the reported level of use of EC varies by demographic composition of participants, context, and differences in EC conceptualisation. One thing is clear, the reported level of awareness of EC in most studies is much higher than the level of use in those studies.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from this study concluded that little more than half (54.8%) of the study participants have a good knowledge about EC this is relatively higher compared to the findings of the study conducted in Arbaminch (21.9%) [ 9 ] and Haramaya (25.7%) [ 26 ], Mizan (34.6%) [ 16 ] (Nigeria (27.8%) [ 29 ]. However the knowledge level is lower in comparison to preparatory schools in Mekelle (75.7%) [ 22 ], Harar (70.0%) [ 20 ] and India (60.1%) [ 30 ].…”
Section: Discussionmentioning
confidence: 77%